Manufacturing and the product cycle a case study of Moran Furniture - Harding, Ben; Donato, Aaron Firth; Colling, Cath; Video Education Australasia (Bendigo, Victoria : Video Education Australasia, 2005)
In this program, Moran Furniture explain the stages in their product cycle - the process that creates their award-winning sofas. The product cycle is examined from the initial concept through product design, production and distribution, marketing and sales
Title from title screen
Executive producer, Mark McAuliffe ; editor, Aaron Firth Donato ; graphics, Grey Laugher ; camera, Nick Hayward
Voice over: Kellie Jones
Keywords: Product life cycle; Product management